The Early Effects of Ontario’s Administrative Driver’s Licence Suspension Law on Driver Fatalities with a BAC > 80 mg% - Mann, Robert E. (Can J Public Health, 2002)
Background: On November 29, 1996, Ontario introduced an Administrative Driver’s Licence Suspension (ADLS) law, which required that anyone charged with driving with a blood alcohol concentration (BAC) over the legal limit of 80 mg% or failing to provide a breath sample would have their licence suspended for a period of 90 days at the time the charge was laid. This study evaluates the early effects of Ontario’s ADLS law on alcohol-involved driver fatalities. Methods: Interrupted time series analysis with ARIMA modelling was applied to the monthly proportion of drivers killed in Ontario with a BAC over 80 mg% for the period Jan. 1, 1988 to Dec. 31, 1997. Results: A significant intervention effect was found, with ADLS being associated with an estimated reduction of 17.3% in the proportion of fatally injured drivers who were over the legal limit. Conclusion: These data provide an early indication that the law resulted in some success in reducing alcohol-related driver fatalities.